2007
DOI: 10.1007/s10803-007-0451-8
|View full text |Cite
|
Sign up to set email alerts
|

The Boundaries of the Cognitive Phenotype of Autism: Theory of Mind, Central Coherence and Ambiguous Figure Perception in Young People with Autistic Traits

Abstract: Theory of Mind, Weak Central Coherence and executive dysfunction, were investigated as a function of behavioural markers of autism. This was irrespective of the presence or absence of a diagnosis of an autistic spectrum disorder. Sixty young people completed the Social Communication Questionnaire (SCQ), false belief tests, the block design test, viewed visual illusions and an ambiguous figure. A logistic regression was performed and it was found that Theory of Mind, central coherence and ambiguous figure varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 21 publications
(20 reference statements)
3
36
0
9
Order By: Relevance
“…There is growing evidence that ASD represents the extreme end of a phenotypical continuum that is expressed to varying levels in both clinically identified and neurotypical populations (Best, Moffat, Power, Owens, & Johnstone, 2008). Additionally, studies exploring subthreshold expression of ASD phenotype traits have not only shown that the cognitive and behavioral characteristics associated with ASD are not confined to those with a diagnosis, but individuals who express elevated levels of these traits are also more susceptible to milder versions of a number of the psychiatric and psychosocial difficulties found in individuals with ASD as well (Best et al, 2008;Kanne, Christ, & Reiersen, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that ASD represents the extreme end of a phenotypical continuum that is expressed to varying levels in both clinically identified and neurotypical populations (Best, Moffat, Power, Owens, & Johnstone, 2008). Additionally, studies exploring subthreshold expression of ASD phenotype traits have not only shown that the cognitive and behavioral characteristics associated with ASD are not confined to those with a diagnosis, but individuals who express elevated levels of these traits are also more susceptible to milder versions of a number of the psychiatric and psychosocial difficulties found in individuals with ASD as well (Best et al, 2008;Kanne, Christ, & Reiersen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies exploring subthreshold expression of ASD phenotype traits have not only shown that the cognitive and behavioral characteristics associated with ASD are not confined to those with a diagnosis, but individuals who express elevated levels of these traits are also more susceptible to milder versions of a number of the psychiatric and psychosocial difficulties found in individuals with ASD as well (Best et al, 2008;Kanne, Christ, & Reiersen, 2009). It has been proposed (Kanne, et al, 2009;Kunihira, Senju, Dairoku, Wakabayashi, & Hasegawa, 2006) that these findings provide evidence to support the feasibility and utility of examining subthreshold expression of the traits associated with the ASD phenotype in neurotypical samples as a proxy for individuals with an ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Even within the cognitive domain, symptoms related to executive functioning on the one hand and focus on detail and the difficulty to integrate information on the other may not be caused by the same underlying principles (see e.g., Best et al 2008;Happé & Booth 2008;Lawson et al 2004). The present findings are consistent with this hypothesis, as different subgroups were clearly identified in the classification behavior.…”
Section: Interpretation Of the Guessing Groupmentioning
confidence: 99%
“…Há três supostos endofenótipos cognitivos que vêm sendo estudados para o autismo: défi -cits de teoria da mente, função executiva e fraca coerência central. Tais hipóteses cognitivas do autismo se propõem a lançar luz a diferentes características centrais ao transtorno (Best, Moffat, Power, Owens, & Johnstone, 2008;Pellicano, Maybery, Durkin, & Maley 2006).…”
unclassified
“…Estes défi cits já foram amplamente documentados na literatura (Best et al, 2008;Pellicano et al, 2006). Considerando-se as evidências de que a herdabilidade no autismo se encontra em torno de 80% (Ronald & Hoekstra, 2011), hipotetiza-se sobre a presença de défi cit de teoria da mente também em familiares de pessoas com autismo.…”
unclassified